An electrochemical immunobiosensor for direct detection of veterinary drug residues in undiluted complex matrices - Khor, S.M.; Liu, G.; Peterson, J.R.; Iyengar, S.G.; Gooding, J.J. (2011)
An electrochemical immunobiosensor is developed that allows the detection of small molecules, such as drugs, in undiluted complex samples, with no washing or rinsing steps via a displacement assay. This is achieved using an interface comprised of a mixed layer of oligo(phenylethynylene) molecular wire (MW), to allow electrochemical communication, and oligo(ethylene glycol) (OEG) to control the interaction of proteins and electroactive interferences with the electrode surface. The mixed layer is formed from in situ-generated aryl diazonium cations. To the distal end of the MW, a redox probe 1,1’-di(aminomethyl)ferrocene (FDMA) is attached followed by an epitope (the structural feature the antibody selectively recognizes) to which an antibody would bind. Association or dissociation of the antibody with the sensing interface causes a modulation of the ferrocene electrochemistry. Antibody complexed electrodes are exposed to samples containing spiked enrofloxacin (unbound target analyte), in milk and environmental water and interrogated using square wave voltammetry (SWV). The lowest detected concentration of free enrofloxacin was 10 pg/mL in phosphate buffer, 50 mM, pH 7. For free enrofloxacin detection in undiluted complex matrices, by adding disodium EDTA (50 mM), the recovery obtained was 94.1 % in skim milk and 88.5 % in stream water, respectively as compared to clean phosphate buffer. The immunobiosensor response time was 10–15 minutes. The sensor performance in milk was shown to be superior to a standard method based on Liquid Chromatography Mass Spectroscopy (LC-MS/MS).